Restauração de florestas que sofreram queimadas recentes através de sistemas agroflorestais - Siqueira, Gabriel Henrique Kükl (Universidade Federal de São Carlos, 2023)
In view of the problem of fires in forest areas, the present study aimed to highlight the importance of environmental restorations through SAFs, as a methodology for the recovery of forests that have suffered recent fires. For this, the concept of successional agroforests was used, that is, with a high density of species, and this model could include several environmental restoration techniques in order to recover degraded areas as quickly as possible, including in critical cases such as areas that were exposed to fire, bringing numerous benefits, both environmental, social and economic. For the development of this work, a bibliographic review was used as a methodology, that is, pre-existing studies were used with the purpose of substantiating the proposed restoration method. Therefore, the methodology employed made it possible to analyze the scope of the use of SAF as a method of forest restoration in areas that suffered fires, relating to the various existing restoration methods; the analysis of the effect of fire in relation to the physical, chemical and biological aspects of the soil and identify areas of restriction to the implementation of SAF according to the current legislation.
Restoration of forests that suffered recent fires through agroforestry systems
Keywords: Sistemas agroflorestais; Restauração florestal; Queimadas; Agroforestry systems; Forest restoration; Forest fire; CIENCIAS AGRARIAS::AGRONOMIA::EXTENSAO RURAL; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::SILVICULTURA::PROTECAO FLORESTAL